EP257/#1025 Does genetic status influence time to death after diagnosis with brain metastasis in ovarian cancer?. (4th December 2022) - Levine, Monica; Haight, Paulina; Fox, Brandon; Espelien, Brenna; Wagner, Vincent; Senter, Leigha; Backes, Floor
Abstract : Objectives: The purpose of this study was to evaluate the impact of BRCA mutation status on survival among patients with epithelial ovarian, primary peritoneal or fallopian tube cancer (EOC) and brain metastasis (BM). Methods: Single institution retrospective study of EOC patients who had access to germline and somatic genetic testing from 2017–2020. Genetic status, oncologic data and demographics were abstracted from medical records. Descriptive statistics were performed. Results: From 2017–2020, 449 patients underwent germline genetic testing, and 308 patients underwent somatic testing. BM incidence was 2.04% (1/49) among germline BRCA (gBRCA) mutated cases, 14.58% (7/48) among somatic BRCA (sBRCA) mutated cases, and 3.41% (12/352) among patients without germline or somatic BRCA mutations (non-BRCA) (p=.001). Median time from initial diagnosis to diagnosis with BM was 38 months for gBRCA, 29 months for sBRCA, and 23 months for non-BRCA cases. Two cases were diagnosed with BM at initial diagnosis. Median time to death after BM diagnosis is not reached for gBRCA, 27 months for sBRCA, and 12.5 months for non-BRCA cases. There was no difference in the number of isolated BM between groups; systemic disease was present at the time of BM diagnosis for 16/20 (80%). Conclusions: This is the first report describing outcomes of EOC with BM incorporating germline and somatic genetic data. BMs were most frequent in sBRCA patients. Survival after BM diagnosis was longest for the gBRCA, followed by sBRCA, and shortest for non-BRCA cases. The presence of BRCA mutations, germline or somatic, may represent a favorable prognostic factor if BM are diagnosed.